Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1192/bjo.2020.56
|View full text |Cite
|
Sign up to set email alerts
|

Premigration social adversity and autism spectrum disorder

Abstract: Background Several studies suggest significant relationships between migration and autism spectrum disorder (ASD) but there are discrepant results. Given that no studies to date have included a pathological control group, the specificity of the results in ASD can be questioned. Aims To compare the migration experience (premigration, migratory trip, postmigration) in ASD and non-ASD pathological control groups, and study the relationships between migration and autism severity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Several reasons have been proposed for the higher prevalence or greater risk for ASD among immigrant populations, including nutrition and vitamin insufficiency (Dealberto, 2011; Lee et al, 2019; Schmidt et al, 2012), stress and trauma from migration (Rai, Golding, et al, 2012), the timing of migration or pregnancy (Kolevzon et al, 2007; Magnusson et al, 2012), and other sociodemographic factors (Kolevzon et al, 2007; Rai, Lewis, et al, 2012). However, other studies have also posited that there is a lower prevalence or lower risk for ASD among children of immigrant parents or no difference in risk when compared to children of non‐immigrant parents (Abdullahi et al, 2019; Augereau et al, 2020; Kamer et al, 2004; Singh et al, 2013). Kamer et al (2004) reviewed census data of children in Israel born between 1983 and 1997 and found that first‐generation Ethiopian children had the lowest prevalence of pervasive developmental disorder when compared to non‐Ethiopian immigrant children, and Israeli born, non‐Ethiopian children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reasons have been proposed for the higher prevalence or greater risk for ASD among immigrant populations, including nutrition and vitamin insufficiency (Dealberto, 2011; Lee et al, 2019; Schmidt et al, 2012), stress and trauma from migration (Rai, Golding, et al, 2012), the timing of migration or pregnancy (Kolevzon et al, 2007; Magnusson et al, 2012), and other sociodemographic factors (Kolevzon et al, 2007; Rai, Lewis, et al, 2012). However, other studies have also posited that there is a lower prevalence or lower risk for ASD among children of immigrant parents or no difference in risk when compared to children of non‐immigrant parents (Abdullahi et al, 2019; Augereau et al, 2020; Kamer et al, 2004; Singh et al, 2013). Kamer et al (2004) reviewed census data of children in Israel born between 1983 and 1997 and found that first‐generation Ethiopian children had the lowest prevalence of pervasive developmental disorder when compared to non‐Ethiopian immigrant children, and Israeli born, non‐Ethiopian children.…”
Section: Introductionmentioning
confidence: 99%
“…Kamer et al (2004) reviewed census data of children in Israel born between 1983 and 1997 and found that first‐generation Ethiopian children had the lowest prevalence of pervasive developmental disorder when compared to non‐Ethiopian immigrant children, and Israeli born, non‐Ethiopian children. Augereau et al (2020) examined whether the migration experience or pre‐migration adversity would be associated with ASD. The authors compared the migration background of parents and grandparents of boys with ASD to boys with language disorders, finding that the migration experience itself was not differentially associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In France, the HDI values of native countries were significantly lower for parents and grandparents of ASD boys compared to controls (parents and grandparents of non-ASD boys with language disorders), especially for paternal grandparents, whereas no differences were found between the two groups when considering only (grand) parental immigrant status. Furthermore, HDI levels from the paternal line (father and especially paternal grandparents) were negatively correlated with autism severity, particularly for social interaction impairments ( 14 ). The authors hypothesized that social adversity-related stress experienced during the premigration period, especially by paternal grandparents, may be a factor of vulnerability for ASD ( 14 ).…”
Section: Differential Exposure To Neurodevelopmental Risk Factorsmentioning
confidence: 99%
“…Furthermore, HDI levels from the paternal line (father and especially paternal grandparents) were negatively correlated with autism severity, particularly for social interaction impairments ( 14 ). The authors hypothesized that social adversity-related stress experienced during the premigration period, especially by paternal grandparents, may be a factor of vulnerability for ASD ( 14 ). Furthermore, associations between low human development and the incidence of schizophrenia (which is nowadays considered a neurodevelopmental disorder), including childhood-onset schizophrenia, have been observed in immigrant populations ( 88 91 ).…”
Section: Differential Exposure To Neurodevelopmental Risk Factorsmentioning
confidence: 99%
“…Thus, members of minority groups do not tend to receive evidence-based interventions at appropriate ages, which points to a significant gap in equity in relation to the cross-ethnic and cross-racial treatment of ASD [ 7 ]. Additionally, in France, the higher prevalence of ASD among French immigrants is associated with higher levels of stress, adversity and trauma experienced in the home country [ 8 ].…”
Section: Introductionmentioning
confidence: 99%